Prescribing sustainability: should UN sustainable development goals be part of the medical, pharmacy, and biomedical education? - Wieërs, Grégoire; Absil, Simon; Maystadt, Isabelle; Nicaise, Charles; Modrie, Pauline; Sibille, François-Xavier; Melly, Ludovic; Dogné, Jean-Michel (Frontiers in Medicine, 2024)
Introduction How to adapt the curriculum of medicine, pharmacy, and biomedical sciences to prepare future health professionals to meet the challenge of maintaining quality care in a period of socio-ecological crisis? Addressing connections between humanity and sustainable environment should include an analysis of the reciprocal influence of various ecosystems, since it is now clear that healthcare systems have an impact on ecosystems and vice versa. Here, we propose that integrating the United Nations Sustainable Development Goals (SDGs) into the curriculum could be a first step in such a transversal education. Methods Members of the faculty of medicine at the University of Namur, Belgium, including teaching staff of the department of medicine, pharmacy, biomedical sciences and psychology, were invited to respond anonymously to a questionnaire about their views on the feasibility of integrating the SDGs into their teaching. A subsequent survey on students’ perceptions of such teaching was conducted by student representatives. Results Seventy-nine percent of surveyed members of the medical faculty believe that it is possible to integrate SDGs into their lectures. However, 44–86% of them did not know how to integrate each individual goal. 94.4% of students would like SDGs to play a greater role in their education; 64.4% of them would integrate them into existing modules; 23.9% would create an optional module, and 11.9% would create a mandatory module. Conclusion Sustainable Development Goals integration into the curriculum of medicine, pharmacy, and biomedical sciences is perceived as challenging in a dense teaching program. To clarify how SDGs can translate into traditional lectures, we provide for each SDG targeted applications for bachelor’s, master’s and continuing education.